The pattern of 1‐aminocyclopropane‐1‐carboxylate oxidase induction in the tomato leaf petiole abscission zone is independent of expression of the ribonuclease‐LX‐encoding LeLX gene. (26th April 2018) - Chersicola, M.; Kladnik, A.; Tušek Žnidarič, M.; Lers, A.; Dermastia, M.
Abstract: The abscission of tomato leaves occurs in the petiole abscission zone, and its late stage includes two spatially divided processes: cell separation and programmed cell death (PCD). Both of these processes are regulated by ethylene. The last step in ethylene biosynthesis is conversion of 1‐aminocyclopropane‐1‐carboxylic acid to ethylene, which is catalysed by the enzyme 1‐aminocyclopropane‐1‐carboxylate oxidase (ACO); however, the location of ACO in the leaf petiole abscission zone is not known. The tomato gene LeLX encodes ribonuclease LX, which is a marker for PCD and is induced by ethylene during abscission, but its association with ACO has not been explored. In a tomato transgenic line 1‐7 with inhibited expression of LeLX showing delayed leaf abscission, the morphology and ultrastructure of the leaf petiole abscission zone was examined. In this zone of the cv.'VF36' and of a transgenic line 1‐7, spatiotemporal differences in expression of LeACO1 and LeACO4 were analysed and ACO protein was detected immunohistochemically. In comparison to wild‐type plants, there were no obvious morphological and ultrastructural features in the abscission zone of plants of a transgenic line 1‐7 before and after abscission induction. LeACO1 expression was low before abscission induction, and increased 24 h after induction, although with no apparent spatial pattern. In contrast, LeACO4 was expressed before abscission induction, and its transcript level declined 24 h after induction on the distal side of the abscission zone fracture. In the LeLX ‐inhibited transgenic line, there were no significant differences in LeACO1 and LeACO4 expression in the petiole abscission zone, in comparison to wild‐type plants. In addition, the ACO protein was immunolocalised to the vascular tissues that traverse the petiole abscission zone in plants of wild type and of a transgenic line 1‐7; and additionally in the plane of future abscission zone fracture of transgenic‐line plants. The results suggest temporal differential expression of the LeACO genes in tomato leaf petioles and vascular localisation of ACO1 protein. Additionally, the results indicate that expression of LeACO genes is not affected by suppression of the LeLX expression.